The Utility of the King-Devick Test in Evaluating Professional Ice Hockey Players with Suspected Concussion. (26th July 2019) - Echemendia, R J; Bruce, J M; Thelen, J; Comper, P; Hutchison, M; Meeuwisse, W
Abstract: Purpose: The King-Devick (KD) is a measure of rapid number naming used in the evaluation of sports-related concussion (SRC). Recent data from the Canadian Football League and Rugby Union suggest that the KD should not be used as a stand-alone measure of SRC. The purpose of this study was to examine the diagnostic utility of the KD in professional ice hockey players. Methods: NHL players who were suspected of having a concussion were evaluated with the KD and either the SCAT3 or the SCAT5. Players who were evaluated and not diagnosed with concussion served as Active controls. A small group of non-Active control players was also tested twice and was included in the present study for comparison. Results: 1605 players were evaluated with the KD at baseline. Of these, 53 were diagnosed with concussion, 76 were Active controls, and 11 were non-Active controls. Concussed players revealed a decline in performance from baseline to acute evaluation, t(52)=3.05, p<.01, d=.42 while Active controls significantly improved, t(75)=2.05, p<.05, d=.24. No significant change between baseline and acute testing was observed for non-Active controls. Using a cut score of any decline in performance from baseline to suspected injury evaluation yielded Sensitivity=64%, Specificity=61%, Positive Predictive Value=53% and Negative Predictive Value=71%. Conclusion: Our data are consistent with previous studies suggesting that while the KD is useful in differentiating concussed and not concussed athletes acutely, the relatively low predictive values indicate that a decline in KD performance should not be used as a standalone measure to diagnose concussion.